Optical coherence tomography in optic disc drusen - Fraser, J. Alexander; Bursztyn, Lulu L. C. D. (Annals of Eye Science, 2020)
Optic disc drusen (ODD) are hyaline deposits in the optic nerve head, occurring in approximately 2% of the population. ODD may be superficial and visible, or buried and either invisible or seen only as elevation of the optic disc, mimicking optic disc edema. Advanced optic nerve imaging, including optical coherence tomography (OCT) can be used to diagnose and characterize ODD with very high resolution. Enhanced depth imaging (EDI-OCT) in particular has emerged as the optimal modality to directly visualize ODD. This modality has led to a greater ability to differentiate ODD from optic disc edema and prevent misdiagnosis or invasive testing. We review the characteristic findings of ODD on OCT, their distinguishing features, and the use of OCT as a biomarker in the neuro-ophthalmic assessment of ODD.